ANALISIS PENERAPAN PENDEKATAN TaRL (TEACHING AT THE RIGHT LEVEL) DALAM PENINGKATAN KEMAMPUAN LITERASI MEMBACA DASAR SISWA DI SDN AIMUAL KABUPATEN SUMBAWA: Penelitian Skripsi - Hakim, Ainul; Kemala Dewi, Nurul; Nurwahidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of the Teaching at the Right Level (TaRL) approach in improving basic reading literacy skills among students at SDN Aimual. The subjects of this study were 10 students from grades 1 to 5. A qualitative approach was employed in this research. Data collection techniques included interviews and documentation. The collected data were analyzed using descriptive analysis, which involved the following steps: (1) data collection, (2) data reduction, (3) data presentation, and (4) drawing conclusions/verification. The results of the study show that the implementation of the TaRL (Teaching at The Right Level) approach proved effective in enhancing students' literacy skills at the school. Supporting factors such as school support, the quality of instruction, and the use of appropriate methods played a significant role in overcoming existing challenges.